Health Informatics Internship: What Are the Students Perceptions Regard Internship Effectiveness? - Anas Ali Alhur (Indonesian Journal Of Educational Research and Review, 2023)
Internship programs allow students to gain practical experience while learning from professionals. Unfortunately, several barriers are associated with internships, including a lack of defined objectives, no guidance or mentorship, poorly defined tasks, strict deadlines, no opportunities for growth or the acquisition of new skills, no networking opportunities, exclusion from meetings, and insufficient training. Thus, this study aimed to evaluate the state of health informatics (HI) internship programs at the University level. The researcher conducted a cross-sectional approach. This study collected data using a questionnaire. The Statistical Package for Social Sciences (SPSS) 26.0 (Version 26) was used in data analysis.The students indicated that internships positively influenced their learning, interpersonal and personal skills, and employment prospects. However, they also encountered some challenges when they intended to meet with the internship coordinator. Some bias may be present in the reporting. Respondents may have inadvertently misinterpreted the questions, inaccurately expressed their opinions, or simply misunderstood them. Finally, the lack of open-ended questions prevented respondents from expressing their opinions comprehensively. The researcher recommended that soft skills should be emphasized in the curriculum for HI and health information management (HIM). The site supervisor must understand the HI field and the interns' responsibilities, allowing them to apply some of what they have learned.